Pharmacoeconomic analysis of lanreotide and prolonged-release octreotide in first- and second-line therapy of acromegaly - I. S. Krysanov; E. V. Makarova; V. Yu. Ermakova; D. V. Kurkin (Фармакоэкономика)
Background. Pharmacoeconomic aspects of somatostatin analogues remain an important topic for discussion. Despite the higher cost of lanreotide compared to octreotide, the former may have an advantage in terms of administration convenience and high efficacy.Objective: to carry out a cost-effectiveness analysis (CEA) of the use of lanreotide and prolonged-release octreotide in adult patients with acromegaly.Material and methods. A cost model for the treatment of acromegaly patients during the period of 2.5 years was developed, accounting for direct medical costs for drugs and surgical intervention. A pharmacoeconomic study by the CEA method and a sensitivity analysis of the model were performed.Results. In real clinical practice of acromegaly treatment, lanreotide enables a more effective remission compared to prolonged-release octreotide (51% vs 24%) under a comparable safety profile. The direct medical costs for a 2.5-year course of lanreotide amounted to 1,466,669.49 rubles per patient with acromegaly compared to 908,272.53 rubles for a course of prolonged-release octreotide. Considering the difference in the amount of 558,096.79 rubles, the course of lanreotide was found to be 25% more expensive. According to CEA results, the cost of achieving remission in 1 patient with acromegaly with lanreotide and prolonged-release octreotide was equal to 2,415,036.25 and 3,676,115.43 rubles, respectively. Therefore, over the period of 2.5 years, the cost saving amounted to 1,261,079.17 rubles (52%). The sensitivity analysis demonstrated the robustness of the initial model against an increase in the price of lanreotide up to 64%, an increase in the frequency of surgery in patients receiving lanreotide up to 302%, and a decrease in the frequency of remissions in patients receiving lanreotide up to 35%.Conclusion. The use of lanreotide in adult patients with acromegaly is a clinically and cost-effective approach in the context of the Russian healthcare system.